Examining The Role Of Estate Factors, Fresh Fruit Bunch Processing And Logistics Efficiency On Oil Extraction Rate - Cheah, Cheng Teik (2021)
The Oil Extraction Rate (OER) is the Key Performance Indicator (KPI) for the oil palm plantations and palm oil mills. The drop of OER performance has raised a big concern to the palm oil sector. Hence, the main research objective of this study is to propose an improved method to increase OER. The specific research objectives are (1) To examine how planting material, the three stages of growth for palm trees and effective collection of loose fruits influence the Theoretical Graded OER; (2) To examine the FFB Grading on the mill ramp, the present Guidelines for FFB Grading, mixing FFB for process and recovering oil influence the Mill Processing OER; (3) To examine how weighing and trash influence the OER, and how distance and lead time cause damage to FFB; and (4) To explore the handling activities that might cause damage to FFB. This study employed a case study approach that involves field observation and interview with guided questions at palm oil plantation and mills. Both field observation and interview with guided question was carried at palm oil plantation and mills located at Miri, Sarawak. On top, the guided question interview was also conducted at palm oil plantation and mills at Sandakan (Sabah), Kemayan (Pahang), and Selama (Perak). The field observation was carried out at Miri (Sarawak) for 30 days. A total of 126 samples were collected for the observation (Miri), and guided questions feedback from another three locations. These data were further analysed to find the correlations of the estate factors, FFB processing and logistics efficiency with OER